Epistemological Perspective on Orientalist Thought and The Originality of The Qur'an - Farida Nur Afifah (Indonesia); Inayah Rohamaniyah (Indonesia); AbdulGafar Olawale Fahm (Ilorin, Nigeria) (Mafatih, 2023)
Differences in views regarding the originality of the Qur’an between classical and contemporary orientalists are increasingly problematic. Library research data collection techniques. The collected data are classified and analyzed using Emmanuel Kant’s epistimological theory. The data sources used consisted of primary sources obtained from several orientalists and secondary sources obtained from several previous studies. The result of this studi, first, teh differences in the view of the orientalists were influenced by three things, namely the main source, methodology, and the validity of the truth used to measure originality of the Qur’an. Second, classical orientalists in their studies tend to be theological in nature, while contemporary orientalists tend to be sociological, anthropological, and do not involve the realm of theology, so the results are more objective. Thrid, the similarity of some contents of the Qur’an is considered normal because the Qur’an is affirmative and complements existing books.